ANALISIS YURIDIS STATUS KEPEMILIKAN TANAH YANG DISENGKETAKAN OLEH PARA PIHAK DITINJAU DARI HUKUM ADAT DI DESA WONDA, KECAMATAN NDORI, KABUPATEN ENDE - Maria Rosalia Sopi; Yossie M Y Jacob; Rini Marselin Kaesmetan (Petitum Law Journal, 2026)
This study aims to analyze the legal status of customary land ownership disputed by conflicting parties in Wonda Village, Ndori Subdistrict, Ende Regency, from the perspective of customary law. The background of the issue is a land dispute involving church representatives and members of a traditional clan over land located behind a church building. The research uses an empirical legal research method with data obtained through interviews, documentation, and literature review. The findings reveal that the primary cause of the dispute is a lack of communication and legal certainty regarding the status of the land, which is rooted in customary inheritance patterns and oral agreements. Furthermore, the absence of written proof of ownership has exacerbated the conflict between the parties. From a positive legal perspective, land ownership must be registered to obtain legal certainty. However, customary law recognizes land based on ancestral inheritance, even without official documentation. The resolution process involved mediation, but challenges arose due to conflicting historical claims and the absence of oath-taking customary procedures. The study concludes that there is an urgent need to harmonize customary and positive legal systems to prevent future land disputes and ensure protection for both communal and individual rights.